2007
DOI: 10.1177/1088868306294587
|View full text |Cite
|
Sign up to set email alerts
|

In Search of East Asian Self-Enhancement

Abstract: A meta-analysis of published cross-cultural studies of self-enhancement reveals pervasive and pronounced differences between East Asians and Westerners. Across 91 comparisons, the average cross-cultural effect was d = .84. The effect emerged in all 30 methods, except for comparisons of implicit self-esteem. Within cultures, Westerners showed a clear self-serving bias (d = .87), whereas East Asians did not (d = -.01), with Asian Americans falling in between (d = .52). East Asians did self-enhance in the methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
443
8
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(487 citation statements)
references
References 112 publications
31
443
8
5
Order By: Relevance
“…Examining the cross-cultural validity of the present findings is particularly important, because there is an ongoing debate about whether members of collectivistic cultures show the same need for self-esteem and the same level of narcissism and self-enhancement bias as do members of individualistic cultures (Cai, Wu, & Brown, 2009;Heine, 2005;Heine & Hamamura, 2007;Heine, Lehman, Markus, & Kitayama, 1999;Sedikides, Gaertner, & Toguchi, 2003;Sedikides, Gaertner, & Vevea, 2005). Therefore, future research should test whether genuine self-esteem and pure narcissism show different relations with depression in collectivistic versus individualistic cultural contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 81%
“…Examining the cross-cultural validity of the present findings is particularly important, because there is an ongoing debate about whether members of collectivistic cultures show the same need for self-esteem and the same level of narcissism and self-enhancement bias as do members of individualistic cultures (Cai, Wu, & Brown, 2009;Heine, 2005;Heine & Hamamura, 2007;Heine, Lehman, Markus, & Kitayama, 1999;Sedikides, Gaertner, & Toguchi, 2003;Sedikides, Gaertner, & Vevea, 2005). Therefore, future research should test whether genuine self-esteem and pure narcissism show different relations with depression in collectivistic versus individualistic cultural contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 81%
“…It is an open question for future research whether the present theorizing will lead to valid predictions also in collectivistic cultures, where social identity might be even more salient than in individualistic cultures. Research by Heine and his colleagues (Heine & Lehman, 1995;Heine & Hamamura, 2007) has demonstrated that people with collectivistic backgrounds (e.g., Asians) will be less prone to use ingroup favorism in order to boost their self-esteem. This might suggest a reduced Failure-as-an-Asset effect in these cultures.…”
Section: Further Limitations and Future Researchmentioning
confidence: 99%
“…For instance, it is well-known that cultures vary in the extent to which the self is viewed as independent versus interconnected with others. In independent cultures (e.g., U.S.), focusing on private, inner attributes might lead to selfenhancement, whereas reflection on the same attributes may lead to self-criticism among interdependent cultures [11]. Independent cultures also view such inner attributes as more critical to the self-concept, whereas interdependent cultures emphasize less-essentialist attributes concerning relations with significant others [12].…”
mentioning
confidence: 99%